Desenvolvimento de compostos poliméricos biodegradáveis modificados com cargas e fibras naturais vegetais - Vieira, Marília Motomura Gonçalves (2010)
Due to environmental and economical concerns, the study and utilization of raw materials coming from natural renewable resources have grown significantly in the last years. The utilization of biodegradable polymers has shown to be a complementary alternative to those materials used in short term applications, due to the fact that they can be biodegraded in soil after thrown away. Besides that, the development of composite materials made of biodegradable polymers and natural fibers reinforcements is a recent object of study and has received great acceptance to disposable applications because these are considered the least aggressive materials to the environment. Taking this into consideration, this work aimed to develop and characterize compounds of biodegradable polymer (Ecobras®) filled and/or reinforced with natural vegetable fillers or fibers (cassava peel, micronized coconut fiber and wood flour). The compounds were characterized in respect to their properties: rheological; thermal; mechanical; structural; morphological and in respect to their biodegradation behavior. The incorporation of the fillers raised the viscosity of the polymeric matrix, making it a bit more difficult to be processed; and changed the mechanical properties of the compounds, without changing their thermal properties. By adding the fillers to the polymeric matrix, the elastic module of the compounds rose at least 50% in respect to the one of the matrix; and the elongation at break decreased. The fillers were considered inert when it comes to thermal properties. However, the fillers showed a poor interfacial adhesion with the polymeric matrix which can be improved by using compatibilizers agents or making superficial treatment to the fillers. All compounds presented great biodegradation rate, which appeared to be dependent on the addition of fibers and fillers (that postpone biodegradation).